Interpreting The Poem Uriduki Unsa by Nizar Qabbani Through Michael Riffaterre's Semiotic Framework - Dwiki Kusuma; Rohanda Rohanda (Gunung Djati Conference Series, 2025)
This research discusses the meaning contained in the poem Urīduki Unṡā by Nizar Qabbani through Michael Riffaterre's semiotic framework. The method used in this research is an analytical descriptive method based on a qualitative paradigm. The researcher uses the concept of heuristic and hermeneutic reading in revealing the meaning of the poetry. The result of this research is that the poetry tells the story of how great someone's hopes are for women. These hopes reflect not only admiration, but also a deep longing for women to be seen as complete, independent, and dignified individuals. The poem emphasizes the emotional, intellectual, and symbolic significance of women in human life. It portrays women as central figures who possess the power to inspire, nurture, and elevate the human spirit. Through poetic language and imagery, Qabbani conveys that women are not merely objects of affection, but rather living representations of beauty, strength, and the greatest wonder of the world for someone.